El incumplimiento de la jornada laboral en relación al descanso forzoso dispuesto en el artículo cincuenta del Código del Trabajo Ecuatoriano - Jerez, Luis Alfonso (2015)
In private and state oil companies, the work carried out in distant places, working for fourteen consecutive days, having a descaso seven days or twenty-seven consecutive days of rest, pointing contravention of Article 47 Labour Code which determines the maximum workday is eight hours a day and forty hours a week. Also notes that the actual work on the ground is six hours a day and can only afford an additional, extraordinary or recovery time giving special protection to workers. Art. 50 of the Labour Code which limits five days a week, ie forty hours per week and designated as days of forced rest on Saturday and Sunday. This type of work is not covered by the Labour Code, this code is very clear that a person should work more than five consecutive days and two, that is, Saturday and Sunday are mandatory rest. Look to the Labour Code is that the person does not suffer from fatigue and occupational accidents are reduced. These forms of work, fourteen days of work for seven of rest or twenty days of work for seven of rest, are not regulated in the Labour Code, by such circumstances it is important to regulate this type or work modality and working code for more adequate employment in these sectors of production application, and is set on Sunday furlough, to thereby not constitutional rights of workers are violated. The type of contract fourteen days of work for seven days off or twenty days of work for seven of rest that are signed between a worker and the company and is not governed by the Labour Code, is contrary to the basis of objective law where rights and duties to be unobserved or violated the legal uncertainty of public and private institutions is generated develop For the legal basis, it becomes essential that the Labour Code contracts fourteen days off work for seven or twenty-seven working days of rest normatice, this will allow the law, that for reasons of work, distribution adequate time work and the implementation of mechanisms that facilitate more flexible use of it; in particular, to make possible the implementation of nonuniform distributions of working time